Measurement of the [eta](1S) production cross-section in ppcollisions at √s=13TeV - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Grabowski, Jascha; Kecke, Matthieu; Leverington, Blake; Malygina, Hanna; Piucci, Alessio; Skidmore, Nicola; Stemmle, Simon; et al. (The European physical journal. C, Particles and fields, 2020)
Using a data sample corresponding to an integrated luminosity of 2.0 $$\, \text {fb} ^{-1}$$fb-1, collected by the LHCb experiment, the production of the $${\eta _{c}} (1S)$$ηc(1S) state in proton-proton collisions at a centre-of-mass energy of $$\sqrt{s} =13$$s=13 $$\, \text {TeV}$$TeV is studied in the rapidity range $$2.0< y < 4.5$$2.0<y<4.5 and in the transverse momentum range $$6.5< p_{\mathrm {T}} < 14.0 \, \text {GeV} $$6.5<pT<14.0GeV. The cross-section for prompt production of $${\eta _{c}} (1S)$$ηc(1S) mesons relative to that of the $${J /\psi }$$J/ψ meson is measured using the